Novel antibodies against RCD-8 as a tool to study processing bodies - Gudkova, D.O.; Panasyuk, G.G.; Nemazanyy, I.O.; Filonenko, V.V. (Вiopolymers and Cell, 2010)
Aim. To develop the model system for processing bodies (PBs) state monitoring and accomplish it in the future as a possible read-out of mTOR activity in mammalian cells. Methods. In course of this study we raised polyclonal antibodies against one of the PBs scaffold proteins – RCD-8 and employed cell imaging technique. Results. It has been shown that the obtained antibodies recognize the intracellular structures, namely PBs. The detected protein co-localized with known marker of PBs – DCP1a, and partly with marker of SGs – CPEB. Conclusions. Based on changes of PBs number and size in cells after exposure to known inductors or inhibitors of PB formation we prove the specificity of generated antibodies and possibility of their application for studies on the processing bodies dynamics controlled by mTOR-dependent signaling. Мета. Розробити модельну систему для вивчення стану процесивних тілець як можливого показника активності mTOR-кінази в клітинах ссавців. Методи. Виділено поліклональні антитіла до одного з основних білків процесивних тілець – RCD-8 із застосуванням методу імуноцитохімії. Результати. Показано, що отримані антитіла розпізнають внутрішньоклітинні структури, надалі ідентифіковані як процесивні тільця. Білок, що детектується антитілами, локалізується разом з відомим маркером процесивних тілець (DCP1a) та частково – з маркером стресових гранул (CPEB). Висновки. На основі даних щодо зміни розмірів і кількості процесивних тілець у відповідь на обробку клітин відомими індукторами та інгібіторами утворення процесивних тілець доведено специфічність зазначених антитіл і підтверджено можливість їхнього використання для дослідження динаміки утворення процесивних тілець під контролем mTOR-залежного сигнального шляху. Цель. Разработать модельную систему для изучения состояния процессивных телец как возможного показателя активности mTOR-киназы в клетках млекопитающих. Методы. Выделены поликлональные антитела к одному из основных белков процессивных телец – RCD-8 с применением метода иммуноцитохимии. Результаты. Показано, что полученные антитела узнают внутриклеточные структуры, идентифицированные далее как процессивные тельца. Детектируемый белок локализуется вместе с известным маркером процессивных телец (DCP1a) и частично – с маркером стрессовых гранул (CPEB). Выводы. На основании данных об изменениях количества и размера процессивных телец в ответ на обработку клеток известными индукторами и ингибиторами образования процессивных телец продемонстрирована специфичность указанных антител и подтверждена возможность их использования для изучения динамики образования процессивных телец под контролем mTOR-зависимого сигнального пути.